Clinical Outcomes after Mix-and-Match Implantation of Extended Depth of Focus and Diffractive Multifocal Intraocular Lenses - Jae Hyuck Lee; Ho Seok Chung; Su Young Moon; So Young Park; Hun Lee; Jae Yong Kim; Hungwon Tchah (Journal of Ophthalmology)
Purpose. To evaluate the clinical outcomes after bilateral mix-and-match cataract surgery using extended depth of focus (EDOF) and diffractive multifocal (DMF) intraocular lenses (IOLs). Setting. Asan Medical Center, Seoul, South Korea. Design. Prospective clinical study. Methods. Thirty-seven patients underwent TECNIS Symfony EDOF IOL (ZXR00) implantation in the dominant eye, and TECNIS +3.25 DMF IOL (ZLB00) implantation in the nondominant eye. Patients were followed up for 3 months; uncorrected and corrected distance visual acuity (UDVA and CDVA), uncorrected intermediate and near visual acuity (UIVA and UNVA), contrast sensitivity, defocus curves, stereopsis, and patient satisfaction were assessed. Results. At 3 months, the mean logarithm of the minimum angle of resolution (logMAR) of UDVA was 0.07 ± 0.09 in EDOF IOL eyes, 0.12 ± 0.11 in DMF IOL eyes, and 0.02 ± 0.05 in both eyes. UIVA was 0.11 ± 0.11 in EDOF IOL eyes, 0.16 ± 0.12 in DMF IOL eyes, and 0.04 ± 0.07 in both eyes. UNVA was 0.25 ± 0.15 in EDOF IOL eyes, 0.22 ± 0.16 in DMF IOL eyes, and 0.13 ± 0.13 in both eyes. Thirty patients (81.1%) were more than satisfied with near vision, and 8 patients (21.6%) complained of severe glare and halo. Spectacle independence for near vision was achieved in 34 patients (91.9%), and 31 patients (83.8%) had better than a 50-second arc of stereopsis. Conclusion. Mix-and-match cataract surgery with EDOF and DMF IOL implantation provided good visual outcomes for all distances. Additionally, excellent patient satisfaction was achieved with a high level of spectacle independence and acceptable photic phenomena.